Justicia glaciar en Los Andes y más allá - Carey, Mark (2020)
Abstract This article introduces the concept of glacier justice as a new way to analyze, understand, and respond to ice loss and climate change in Peru, the Andes, and internationally. Glacier justice explores complex societal dynamics, multiple storylines, and diverse interactions across communities and with glaciers, water, hazards, and climate -- rather than simply lamenting lost ice or documenting its decline. The concept is built on work in both environmental justice and the environmental humanities to expose systematic forms of inequality and injustices, and to let communities drive research questions and directions. The article focuses on three main approaches to help advance glacier justice: (1) community-led research as opposed to community participation; (2) the incorporation of diverse forms of knowledge; and (3) a deeper analysis and understanding of vulnerability to avoid deterministic and linear ideas that center on technoscientific expertise.